Analisis Produk Hasil Kelola dan Pemanfaatan Sisa Nasi Oleh Tim Baqiyaturruz di Ponpes Darullughah Wadda’wah - Akbar, Aziz; Robi'in, Muhammad; Fauzi, Nur (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2023)
The rapidly growing Darullughah Wadda'wah Islamic Boarding School has resulted in an increase in the amount of food, especially cooked rice as a staple food. However, the amount of leftover food is also increasing because there is a lot of uneaten food. This causes rice waste to pile up and cause air pollution. This research aims to examine the potential and benefits of the products managed by the Baqiyaturruz Team which are produced from rice leftovers and to find out how many types of products the Baqiyaturruz Team has produced from rice leftovers and to find out the inhibiting and supporting factors. in improving the management and utilization of rice waste at the Darullughah Wadda'wah Islamic Boarding School. This research uses a qualitative descriptive method by looking directly at the field. The research results show that the Baqiyaturruz Team's products are the result of managing and utilizing leftover rice which is produced into karak and snacks. The enthusiasm and creativity of the members as well as the support from the students and administrators of the Darullughah Wadda'wah Islamic Boarding School are supporting factors in utilizing rice waste. However, the lack of support and trust from several related parties, as well as uncertain weather, are the main inhibiting factors in managing and utilizing leftover rice into a product.